Intersectionality Gets Fashionably Fat: Arts-Based Approaches to Gender, Fat and Fashion - Friedman, May; Evans, Calla; Barry, Ben (Art/Research International)

(untitled) (University of Alberta, 2023)
The authors’ research project, Sizing Up Gender, explored the experiences of thirteen participants at the intersections of gender expression and fat. Through a series of photographs of participants and their garments, the project pushed the boundaries of art, identities, representations, and research. This article seeks to consider the ways in which innovative arts-based practice with a deep focus on justice and anti-oppression can allow for a thickening of intersectionality research. The blending of art and research practices, such as those under discussion here, can simultaneously maintain a commitment to the genesis of intersectionality’s critical potential while allowing the term to evolve and consider heretofore undiscussed terrain.